Leader-Member Exchange and Employee Performance: The Mediating Role of Work Engagement and Job Satisfaction - Siswadi, Yudi; Farisi, Salman; Arif, Muhammad; Astuti, Rini (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2025)
Purpose — This study investigates and evaluates the direct or indirect effects of leader-member exchange on work engagement and job satisfaction on employee performance.Methodology — This study adopts a causal approach, examining causal relationships between variables. It involved 200 employees from a Pharmaceutical Company in Medan, North Sumatra, Indonesia, with a sample size of 197 employees. Questionnaires were employed in this study's data collection process. Smartpls (Partial Least Squares) 3.0 software was utilised for structural equation modelling in statistical analysis.Findings — The findings of this study reveal that direct leader-member exchange, work engagement, and job satisfaction significantly affect employee performance. Leader-member exchange significantly affects performance through work engagement and employee job satisfaction at the Pharmaceutical Company in Medan, North Sumatra, Indonesia.Originality/Novelty — This study's novelty highlights the mediating role of work engagement and job satisfaction in the relationship between Leader-Member Exchange (LMX) and employee Performance improvement, providing new insights into such psychological mechanisms.Implications — This research provides information for the Pharmaceutical Company in Medan, North Sumatra, Indonesia, and related parties to improve employee performance by increasing job satisfaction and work engagement and improving existing leadership to provide employee comfort.